Prevalence and Risk Factors of Primary Malnutrition in Children Below 5 Years of Age - Saba Wamiq, Sidra Shahid, Asif Javeed, Iram Nawaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out the prevalence and risk factors of primary malnutrition among children below 5 years of age visiting outpatient department of a tertiary care hospital. Study Design: A cross-sectional study. Place and duration: Department of Pediatric Medicine, Ibn-e-Siena Hospital, Multan from 1st January 2022 to 30th June 2022. Methodology: A total of 151 children of either gender aged below 5 years visiting outpatient department of pediatrics. At the time of enrollment, socio-demographic as well as anthropometric characteristics were noted. Z-score were calculated to label malnutrition considering weight for height criteria according to “World Health Organization (WHO)” charts as: mild, -1.0 to -1.9, moderate, -2.0 to 2.9, and severe, ≤ -3.0. Results: In a total of 151 children, 78 (51.7%) were girls. The mean age, weight and height were 2.67±1.56 years, 10.18±3.55 kg and 82.99±16.39 cm. The mean birth weight was 2.44±0.21 kg. Exclusive breast-feeding for the first 6 months was reported in 69 (45.7%) children while cow’s mild before 1 year of age was reported by 101 (66.9%). The mean height for weight Z-score was calculated to be -1.40±2.20. Distribution of nutritional status revealed that 61 (40.4%) were normal while mild, moderate and severe malnutrition were observed among 37 (24.5%), 11 (7.3%) and 42 (27.8%) children respectively. Malnutrition status had significant association with increasing age (p<0.001), poor maternal educational status (p=0.034) and use of cow’s milk before 1 year of age (p=0.004). Practical Implications: There is a massive need to identify causes behind factors linked with primary malnutrition among children below 5 years of age so that targeted interventions could be planned. Conclusion: The prevalence of primary malnutrition was very high among children below 5 years of age. Age, poor maternal educational status and use of cow’s milk before 1 year of age had significant association with malnutrition. Keywords: Breastfeeding, maternal education, malnutrition, socio-economic status, Z-score.